EFEKTIVITAS MEDIA BOOKLET CEGAH DIARE TERHADAP PERUBAHAN PENGETAHUAN DAN SIKAP IBU BALITA DI POSYANDU MELATI I KELURAHAN KUBU DALAM PARAK KARAKAH KOTA PADANG - Mahira, Hilya; Novelasari, Novelasari; Sumihardi, Sumihardi; Maria Lestari Silaban, Evi; Zicof, Erick (Poltekkes Kemenkes Bengkulu, 2025)
Background: Diarrhea is a major global health problem that often affects children under five. In West Sumatra, 1,910 cases were reported in 2023, while in Padang City cases increased from 1,199 in 2022 to 1,576 in 2023. In the first half of 2025, Parak Karakah Health Center recorded 50 cases among under-fives. Objective: This study aimed to assess the effectiveness of a booklet in improving mothers’ knowledge and attitudes toward diarrhea prevention. Method: A mixed-method design was used, combining an exploratory case study and a quasi-experimental one-group pretest–posttest design. The study was conducted from December 2024 to June 2025 in Kubu Dalam Parak Karakah, Padang City, using interviews and questionnaires. Qualitative data were analyzed through reduction, presentation, and verification, while quantitative data were tested for validity, reliability, normality, and significance using the Wilcoxon test. Results: The booklet was developed using the P-Process. Mothers’ median knowledge increased from 11.00 to 14.00, and attitudes from 48.00 to 67.00. The Wilcoxon test showed a significant change (p=0.0001). Conclusion: The booklet was effective in enhancing mothers’ knowledge and attitudes about diarrhea prevention and is recommended as a practical educational tool in health promotion. recommended that the booklet be further developed according to the target group’s needs and utilized as an educational tool in promotive and preventive health efforts. Keywords: Booklet, Mother, Diarrhea, Knowledge, Attitude